Molecular and Biotechnological Advancements in Hypericum Species (2017)
Hypericum is an important genus of the family Hypericaceae and includes almost 500 species of herbs, shrubs and trees. Being the home for many important bioactive compounds, these species have a long traditional value as medicinal plants. Currently, several species of this genus have been used in ailments as knowledge-based medicine in many countries. In the recent past, several pharmacological studies have been performed using crude extracts to evaluate the traditional knowledge. Results of those studies have revealed that Hypericum extract exert multiple pharmacological properties including antidepressant, antimicrobial, antitumor and wound healing effects. Phytochemical analyses revealed that these species produce a broad spectrum of valuable compounds, mainly naphthodianthrones (hypericin and pseudohypericin), phloroglucinols (hyperforin and adhyperforin), flavonoids (hyperoside, rutin and quercitrin), benzophenones/xanthones (garcinol and gambogic acid), and essential oils. Noticeably, Hypericum perforatum extracts have been used to treat mild to moderate depression from ancient to present times and the antidepressant efficacy of Hypericum extracts has been attributed to its hyperforin content, which is known to inhibit the re-uptake of aminergic transmitters such as serotonin and noradrenaline into synaptic nerve endings. Neurodegenerative diseases and inflammatory responses are also linked with Reactive Oxygen Species (ROS) production. A wide range of flavonoids present in Hypericum extracts, namely, rutin, quercetin, and quercitrin exhibit antioxidant/free radical scavenging activity. Hypericin, beside hyperforin, is the active molecule responsible for the antitumor ability of Hypericum extracts and is seen as a potent candidate to treat brain tumor. Recent attempts of using hypericin in patients with recurrent malignant brain tumors showed promising results. Collectively, Hypericum species contain multiple bioactive constituents, suggesting their potential to occupy a huge portion of the phytomedicine market. Today, studies on medicinal plants are rapidly increasing because of the search for new active molecules, and for the improvement in the production of plants and molecules for the herbal pharmaceutical industries. In the post genomic era, application of molecular biology and genomic tools revolutionized our understanding of major biosynthetic pathways, phytochemistry and pharmacology of Hypericum species and individual compounds. This special issue mainly focuses on the recent advancements made in the understanding of biosynthetic pathways, application of biotechnology, molecular biology, genomics, pharmacology and related areas.